Exploring the Use of Infographics in Fostering Critical Thinking Skills (in a Listening Course) among Fifth Semester English Department Students at UIN Madura - Nur Kamilah; Achmad Baidawi (Journal of English Development, 2026)
This study aims to explore how infographic-based tasks foster critical thinking skills among fifth-semester English Department students at UIN Madura in a Listening course. Responding to the growing demand for 21st-century skills in higher education, this study emphasizes the importance of engaging students in analyzing, evaluating, and interpreting multimodal information beyond traditional text-based materials. A descriptive qualitative approach was employed, involving 15–20 students and one lecturer selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and analysis of students’ infographic products, and were analyzed using thematic analysis with triangulation to ensure data validity. The findings reveal that infographic tasks support students’ critical thinking by encouraging analysis, evaluation, organization of ideas, and synthesis of listening content into meaningful visual representations. Students also reported increased motivation and engagement, although challenges related to design skills and the authenticity of student work were identified. This study contributes to EFL pedagogy by demonstrating the pedagogical value of infographics as an effective multimodal learning tool that supports higher-order thinking in Listening instruction and offers practical implications for integrating visual media into language classrooms.